2016
DOI: 10.1111/dgd.12261
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hydrostatic pressure maintains and enhances the chondrogenic differentiation of cartilage progenitor cells cultivated in alginate beads

Abstract: The objective of this study was to explore the effects of intermittent hydrostatic pressure (IHP) on the chondrogenic differentiation of cartilage progenitor cells (CPCs) cultivated in alginate beads. CPCs were isolated from the knee joint cartilage of rabbits, and infrapatellar fat pad-derived stem cells (FPSCs) and chondrocytes (CCs) were included as the control cell types. Cells embedded in alginate beads were treated with IHP at 5 Mpa and 0.5 Hz for 4 h/day for 1, 2, or 4 weeks. The cells' migratory and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 40 publications
2
55
0
Order By: Relevance
“…This indicates the importance of early matrix formation, especially pericellular matrix, to enable transmission of the compressive force (mechanotransduction), mimicking that produced in in vivo cartilage. Similar results have been found varying the point of hydrostatic loading on differentiating chondrogenic MSCs (Li et al, 2012;Li et al, 2016 In contrast to compressive and shear loading studies, application of hydrostatic pressure at the onset produces more matrix formation (GAG, collagens I, II) and increased mechanical properties (Young's and dynamic modulus) as compared to pre-differentiated MSCs. Despite no in-depth studies regarding the effect of different periods of pre-differentiation, it may be hypothesised that hydrostatic pressure has a larger effect on MSC chondrogenesis during its early stages as suggested in computational/theoretical models, whilst compressive loading exerts its influence on pre-differentiated MSCs, specifically at later stages of chondrogenesis.…”
Section: Chondrogenic Msc Pre-differentiation and Response Under Hydrsupporting
confidence: 69%
See 2 more Smart Citations
“…This indicates the importance of early matrix formation, especially pericellular matrix, to enable transmission of the compressive force (mechanotransduction), mimicking that produced in in vivo cartilage. Similar results have been found varying the point of hydrostatic loading on differentiating chondrogenic MSCs (Li et al, 2012;Li et al, 2016 In contrast to compressive and shear loading studies, application of hydrostatic pressure at the onset produces more matrix formation (GAG, collagens I, II) and increased mechanical properties (Young's and dynamic modulus) as compared to pre-differentiated MSCs. Despite no in-depth studies regarding the effect of different periods of pre-differentiation, it may be hypothesised that hydrostatic pressure has a larger effect on MSC chondrogenesis during its early stages as suggested in computational/theoretical models, whilst compressive loading exerts its influence on pre-differentiated MSCs, specifically at later stages of chondrogenesis.…”
Section: Chondrogenic Msc Pre-differentiation and Response Under Hydrsupporting
confidence: 69%
“…In agreement with these results, Safeshaken et al 2012, using a pellet culture model, demonstrated no increase in chondroinduction without TGF-β addition using a loading regime (0-5 MPa at 0.5 Hz for 4 h/d) for 10 d only. Thus, whether hydrostatic pressure alone is sufficient to induce chondrogenesis to any significant degree remains unresolved (Carroll et al, 2014;Finger et al, 2007;Li et al, 2012;Li et al, 2009;Puetzer et al, 2013;Vinardell et al, 2012;Ye et al, 2014) (Table 2).…”
Section: Tgf-β Presence and Endogenous Production In Pressure-stimulamentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that the changes in HP alone, DS alone, and combined HP and DS followed by off‐loading altered the cell proliferation capacity and metabolism of ECM of hACs within an agarose hydrogel. In most studies conducted to clarify the effects of physical stresses on articular cartilage, a cartilage explant model has been used to apply compressive stresses ex vivo (Elder et al, ; Li et al, ; Sun et al, ). This explant model could reproduce compressive stresses within relatively short regimens; however, this model was often limited by its irregular sample shape due to deformation caused by overloading and/or frequent cycle of loading.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we sought to understand the roles of these stresses on metabolic turnover by chondrocytes. Recently, the effects of compressive stresses on metabolic functions in articular cartilage have been investigated extensively using alginate (Elder et al, ; Li, Zhou, Yang, Jiang, & Gui, ) or agarose (Chowdhury, Bader, Shelton, & Lee, ; Pingguan‐Murphy & Nawi, ) in vitro and ex vivo models (Kraft et al, ; Pascarelli, Collodel, Moretti, Cheleschi, & Fioravanti, ). However, these models could not adequately reproduce stress‐loaded cells and tissue to investigate the effects of pure HP, pure DS, and their combination on the metabolic profile of chondrocytes.…”
Section: Introductionmentioning
confidence: 99%